The Economic Impact of Achievement Gaps in Pennsylvania's Public Schools - Karoly, Lynn A. (RAND Corporation, 2015)
This study documents the magnitude of the gaps in education performance across public school students in Pennsylvania classified by race-ethnicity and socioeconomic status as measured by standardized achievement tests in eighth grade and high school graduation rates. The economic consequences of these gaps are quantified in terms of lost earnings for the low-performing groups and diminished economic output for the state.